Failure analysis of reinforced concrete structures subjected to chloride penetration and reinforcements corrosion - Liberati, Elyson A.P.; Nogueira, Caio G. [UNESP]; Leonel, Edson D.; Chateauneuf, Alaa (Elsevier, 2016)
Structural durability is an important design criterion, which must be assessed for every type of structure, especially for reinforced concrete (RC) structures. When RC structures are located in aggressive environments, its durability is strongly reduced by physical/chemical/mechanical processes that trigger reinforcements corrosion. Among such processes, the diffusion of chlorides is recognized as one of major responsible of corrosion phenomenon start. In this context, this study presents a nonlinear formulation based on the finite element method applied to mechanical analysis of RC structures subjected to chloride penetration and reinforcements corrosion. The physical nonlinearity of concrete is described by Mazars damage model whereas for reinforcements elastoplastic criteria are adopted. The steel loss along time due to corrosion is modeled using an empirical approach and the chloride concentration growth along structural cover is represented by Fick's law. The proposed model is applied to analysis of bended structures. The results obtained by the proposed nonlinear approach are compared to responses available in literature in order to illustrate the evolution of structural resistant load after corrosion starts.
Keywords: Corrosion of reinforcements; Fick's law; Finite element method; Mazars damage criterion; Reinforced concrete